559 - Neuropsychiatric symptomatology after severe COVID-19 in older survivors. (October 2021) - Martins, Sónia; Ferreira, Ana Rita; Fernandes, Joana; Vieira, Tatiana; Fontes, Liliana; Coimbra, Isabel; Paiva, José Artur; Fernandes, Lia
Abstract : Background: The coronavirus disease 2019 (COVID-19) has rapidly spread worldwide, leading to increased concerns about long-term patients' neuropsychiatric morbidity. Currently, there is still few data regarding mental health after hospital discharge of severe COVID-19 elderly patients. Considering this, the present study aims to characterize the neuropsychiatric morbidity in old severe COVID-19 patients. Methods: In the context of an ongoing multidisciplinary research project, this study analyzed a subsample of patients aged ≥60 years, admitted due to COVID-19, during the first wave, in the Intensive Care Medicine Department (ICMD) of a University Hospital in Porto, Portugal. ICMD length of stay (LoS) ≤24h, terminal illness, major auditory loss or inability to communicate at the time of follow- up were used as exclusion criteria. Participants were evaluated by telephone in average 99 (±32) days after being discharged from the hospital, with Six-item Cognitive Impairment Test, PatientHealth Questionnaire and Generalized Anxiety Disorder Scale. Sociodemographic and relevant clinicaldata were obtained from hospital electronic records and clinical interview. Results: A sample of 39 survivors with a mean age of 70 (±6.3) years old were assessed. The majority were male (62%), married (64%), retired (77%), with low educational level (59%), and 15% lived alone. The average number of comorbidities and the daily medications per patient were 4.7 (±1.7) and 5.5 (±3.5), respectively. During ICMD stay, 69% had nosocomial infections and 56% delirium. Deep sedation was used in 74% of the patients (mean=30 days) and 74% needed Invasive Mechanical Ventilation. ICMD mean LoS was33 (±28.3) days. Based on follow-up assessment, 18% of survivors had cognitive impairment, whereas23% and 15% had depressive and anxiety symptoms, respectively. A positive and high correlation between depression and anxiety was found (rs=0.792; p<0.001). No significant associations were observed with cognitive impairment. Conclusions: The presence of this symptomatology may hinder a successful recovery once the patient is discharged back home. This is particularly relevant accruing the strong relationship between depressive and anxious symptoms found in this sample. Therefore, early screening and timely multidisciplinary support interventions to minimize these neuropsychiatric symptoms after discharge should be considered in order to achieve positive health outcomes.